Reactivation of Magma Pathways: Insights From Field Observations, Geochronology, Geomechanical Tests, and Numerical Models. Issue 5 (24th May 2021) - Thiele, Samuel T.; Cruden, Alexander R.; Zhang, Xi; Micklethwaite, Steven; Matchan, Erin L.
Abstract: Field observations and unmanned aerial vehicle surveys from Caldera Taburiente (La Palma, Canary Islands, Spain) show that pre‐existing dykes can capture and re‐direct younger ones to form multiple dyke composites. Chill margins suggest that the older dykes were solidified and cooled when this occurred. In one multiple dyke example, an 40 Ar/ 39 Ar age difference of 200 kyr was determined between co‐located dykes. Petrography and geomechanical measurements (ultrasonic pulse and Brazilian disc tests) show that a microscopic preferred alignment of plagioclase laths and sheet‐like structures formed by non‐randomly distributed vesicles give the solidified dykes anisotropic elastic moduli and fracture toughness. We hypothesize that this anisotropy led to the development of margin‐parallel joints within the dykes, during subsequent volcanic loading. Finite element models also suggest that the elastic contrast between solidified dykes and their host rock elevated and re‐oriented the stresses that governed subsequent dyke propagation. Thus, the margin‐parallel joints, combined with local concentration and rotation of stresses, favored the deflection of subsequent magma‐filled fractures by up to 60° to form the multiple dykes. At the edifice scale, the capture and deflection of active intrusions by older ones could change the organization of volcanic magma plumbing systems and cause unexpected propagation paths relative to the regional stress. We suggest that reactivation of older dykes by this mechanism gives the volcanic edifice a structural memory of past stress states, potentially encouraging the re‐use of older vents and deflecting intrusions along volcanic rift zones or toward shallow magma reservoirs. Key Points: Dykes form significant and highly oblique mechanical discontinuities in volcanic edifices Local stresses and mechanical anisotropy within solidified dykes can capture and deflect subsequent intrusions to form a multiple‐dyke Reactivation of magma pathways by these mechanisms influences the emergent organization of magma plumbing systems